2009
DOI: 10.1190/1.3033214
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative comparison of processes of oil- and water-based mud-filtrate invasion and corresponding effects on borehole resistivity measurements

Abstract: Some laboratory and qualitative studies have documented the influence of water-based mud͑WBM͒-filtrate invasion on borehole resistivity measurements. Negligible work, however, has been devoted to studying the effects of oil-based mud͑OBM͒-filtrate invasion on well logs and the corresponding impact on the estimation of petrophysical properties. We quantitatively compare the effects of WBM-and OBM-filtrate invasion on borehole resistivity measurements. We simulate the process of mud-filtrate invasion into a poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…The water saturation suggests that the invasion is a gradual transition zone instead of a piston-like interface ( Figure 5b). The extent of the gradual change of the water The numerical simulation of the mud invasion was run for 100 h. The results overall agree with previous work (Salazar and Torres-Verdín, 2008) and verify the numerical model. Figures 4d-4f show that the permeability and porosity of the mud cake are nearly constant at 0.01 mD and 0.2, respectively, despite the fl uctuations in the pressure drop across the mud cake.…”
Section: Case Studysupporting
confidence: 69%
See 1 more Smart Citation
“…The water saturation suggests that the invasion is a gradual transition zone instead of a piston-like interface ( Figure 5b). The extent of the gradual change of the water The numerical simulation of the mud invasion was run for 100 h. The results overall agree with previous work (Salazar and Torres-Verdín, 2008) and verify the numerical model. Figures 4d-4f show that the permeability and porosity of the mud cake are nearly constant at 0.01 mD and 0.2, respectively, despite the fl uctuations in the pressure drop across the mud cake.…”
Section: Case Studysupporting
confidence: 69%
“…Previous studies concluded that the outer mud cake on the well wall is much thicker than the inner mud cake that penetrates into the pores near the well in the case of water-based mud invasion (Salazar and Torres-Verdín, 2008;Wang et al, 2009). Therefore, we only consider the outer mud cake because of the assumption of water-based mud invasion in this study.…”
Section: Mathematical Modelmentioning
confidence: 96%
“…These maps are used to simulate borehole array-induction resistivity measurements, which can be used to rank rock quality within a reservoir. For an extended explanation of this methodology, the reader is referred to Salazar and Torres-Verdín (2009).…”
Section: Simulation Of Resistivity With a Dynamic Mud-filtrate Invasimentioning
confidence: 99%
“…In general, oil-based mud invasion is shallower than invasion caused by water-based mud. However, invasion with SOBM can be radially deep enough to affect borehole array-induction resistivity measurements (La Vigne et al, 1997;Salazar et al, 2011;Malik et al, 2008;Salazar and Torres-Verdín, 2009). Both mud and rock properties control the dynamic growth of mud cake and the time evolution of fluid displacement (Wu et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
“…When the formation geometry is more complex, however, the relation between apparent resistivity and the actual resistivity distribution is not obvious. In addition, borehole effects [20,22], and invasion by drilling mud [13,28] can further affect the measurements.…”
Section: Introductionmentioning
confidence: 99%